Katarsis Pencipta pada Lirik Lagu Langit Malam Karya Chou Senka: Analisis Psikoanalisis - Puspo Ramadhani (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
Song lyrics often serve as a medium for expressing the psychological experiences and emotions of their creators. One example is Langit Malam, a song written by Chou Senka that reflects various personal emotional experiences. This study aims to identify the representation of the songwriter’s psychological condition, analyze the dynamics of the id, ego, and superego, and explain the form of catharsis reflected in the lyrics of Langit Malam. This research employed a qualitative descriptive method using Sigmund Freud’s psychoanalytic approach. The primary data consisted of the song lyrics, while supporting data were obtained through interviews with the songwriter. Data were analyzed through collection, reduction, presentation, and conclusion drawing. The findings reveal that the lyrics represent psychological conditions such as anxiety about the future, psychological pressure, loneliness, and overthinking tendencies. The psychoanalytic analysis shows interactions among the id, ego, and superego in shaping responses to personal experiences. The id is reflected in the desire to escape pressure and seek comfort, the ego in efforts to confront reality, and the superego in awareness of responsibilities and life demands. The study also finds that the songwriting process functions as a means of channeling emotional experiences. Thus, Langit Malam can be understood as a form of catharsis that allows emotional release through artistic creation. These findings show that song lyrics can be a medium for understanding the relationship between psychological experience and the creative process.